PREDICTIVE VALUE OF OCULAR TRAUMA SCORE IN OPEN GLOBE COMBAT EYE INJURIES - Islam, Qamar ul; Ishaq, Mazhar; Yaqub, Muhammad Amer; Mehboob, Muhammad Asim (Journal of Ayub Medical College Abbottabad, 2016)
Background: Prediction of final visual outcome in ocular injuries is of paramount importance and various prognostic models have been proposed to predict final visual outcome. The objective of this study was to validate the predictive value of ocular trauma score (OTS) in patients with combat related open globe injuries and to evaluate the factors affecting the final visual outcome. Methods: Data of 93 patients admitted in AFIO Rawalpindi between Jan 2010 to June 2014 with combat related open globe ocular injuries was analysed. Initial and final best corrected visual acuity (BCVA) was categorized as No Light Perception (NLP), Light Perception (LP) to Hand Movement (HM), 1/200-19/200, 20/200-20/50, and ‰¥20/40. OTS was calculated for each eye by assigning numerical raw points to six variables and then scores were stratified into five OTS categories. Results: Mean age of study population was 28.77±8.37 years. Presenting visual acuity was <20/200 (6/60) in 103 (96.23%) eyes. However, final BCVA of ‰¥20/40 (6/12) was achieved in 18 (16.82%) eyes, while 72 (67.28%) eyes had final BCVA of <20/200 (6/60). Final visual outcome in our study were similar to those in OTS study, except for NLP in category 1 (81% vs. 74%) and ‰¥20/40 in category 3 (30% vs. 41%). The OTS model predicted visual survival (LP or better) with a sensitivity of 94.80% and predicted no vision (NLP) with a specificity of 100%. Conclusion: OTS is a reliable tool for assessment of ocular injuries and predicting final visual outcome at the outset. Keywords: Ocular Trauma; Ocular Trauma Score (OTS); Open Globe Injury; Visual Acuity